The Influence of Global Liquefied Natural Gas (LNG) Price Instability on Indonesia's Balance of Payments Dynamics - Muhammad Fery Hidayat; Wulandari Pryangan; Sri Rachmawati Rachman (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2025)
The evolution of the global energy landscape has established liquefied natural gas (LNG) as a critical component of the worldwide energy mix. Nonetheless, instability in global LNG prices presents significant challenges, particularly for export dependent nations like Indonesia. This study rigorously quantifies the impact of LNG price volatility on Indonesia’s Balance of Payments (BOP) and subsequently proposes strategic policies to bolster national economic resilience. Utilizing a mixed-methods design, the research integrates advanced time-series econometric modeling specifically Vector Autoregression (VAR) and Impulse Response Function (IRF) analysis with a qualitative policy review spanning the period 2015–2024. Data include monthly LNG indices, BOP components, and macroeconomic controls, sourced from authoritative institutions such as the International Energy Agency (IEA, 2024), Bank Indonesia (2024), and the Ministry of Energy and Mineral Resources (2024). The empirical results demonstrate a significant, adverse effect of LNG price shocks on Indonesia's trade balance and overall current account, with these effects propagating and persisting over multiple quarters (Fauzi & Gunawan, 2023; Siregar et al., 2023). These findings underscore Indonesia’s high vulnerability to global commodity fluctuations and emphasize the urgent requirement for robust fiscal buffers and economic diversification strategies. Policy analysis reveals ongoing government efforts in energy subsidy reform and infrastructure investment but highlights continuing difficulties in reconciling energy security with overall macroeconomic stability (Robinson, 2023; UNCTAD, 2025). This comprehensive investigation contributes new empirical evidence and practical policy recommendations, establishing a valuable framework for managing LNG price shocks in Indonesia and analogous emerging markets.